PERBANDINGAN TINGKAT KUALITAS PRODUK SAYURAN PADA PASAR TRADISIONAL DAN PASAR MODERN DI NGALIYAN KOTA SEMARANG DALAM PERSPEKTIF BIOLOGI - Pradjasasmitha, Malika Allfathania; Udzmah, Nikmatul; Saputri, Septia Dwi; Naima, Mirtaati; Hidayatullah, Ahmad Fauzan (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2023)
Vegetables are an important source of nutrients in the fulfillment of essential nutrients for human health. The selection of quality vegetables is the main key in ensuring maximum nutritional benefits. Traditional markets and modern markets offer different approaches to quality including freshness, nutritional composition, price, shelf life and safety in confectionery. Therefore, this study aims to compare the quality of vegetables in traditional markets and modern markets by considering biological factors such as surface texture, color, freshness, and integrity of the selected vegetable samples. The research method used is a qualitative descriptive method consisting of identifying issues and objectives, collecting data, analyzing, and formulating concepts. Data collection by taking samples from one of the populations as the main data collection tool to compare the quality of vegetables in traditional markets with modern markets in Ngaliyan District, Semarang City from a biological perspective. In this study the samples used in the study were taken from five different types of vegetables, namely tomatoes, carrots, pakcoy, potatoes, and leeks. The results showed that the comparison of the quality of vegetables owned by traditional markets tends to be fresher and has a higher nutritional content compared to Superindo Modern Market. This is due to the harvesting process that is closer to the time of sale in traditional markets, so that the nutrients in vegetables are still well preserved. On the other hand, vegetables sold in Superindo Modern Market often undergo a longer preservation and transportation process, so that their nutritional content can be reduced.